2018
DOI: 10.1519/jsc.0000000000002553
|View full text |Cite
|
Sign up to set email alerts
|

Are Change-of-Direction Speed and Reactive Agility Independent Skills Even When Using the Same Movement Pattern?

Abstract: Čoh, M, Vodičar, J, Žvan, M, Šimenko, J, Stodolka, J, Rauter, S, and Maćkala, K. Are change-of-direction speed and reactive agility independent skills even when using the same movement pattern? J Strength Cond Res 32(7): 1929-1936, 2018-The purpose of this investigation was to determine whether there are differences between the 2 approaches to quantifying agility (preplanned vs. unplanned response) when reacting to a stimulus in an identical spatial scenarios. The study involved 45 male and 31 female trained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 19 publications
5
38
0
Order By: Relevance
“…Agility is a significant component of athletic performance as it encompasses the ability to perform whole-body and local movements rapidly, effectively, and efficiently [10][11][12][13][14]. While the classic definition of agility is understood as the ability to change the direction or speed of a movement both quickly and precisely, more recent definitions have integrated a cognitive component.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Agility is a significant component of athletic performance as it encompasses the ability to perform whole-body and local movements rapidly, effectively, and efficiently [10][11][12][13][14]. While the classic definition of agility is understood as the ability to change the direction or speed of a movement both quickly and precisely, more recent definitions have integrated a cognitive component.…”
Section: Introductionmentioning
confidence: 99%
“…While the classic definition of agility is understood as the ability to change the direction or speed of a movement both quickly and precisely, more recent definitions have integrated a cognitive component. This encompasses factors such as anticipation, visual and perceptual recognition, reaction speed, and attention skills [14,15]. Both agility definitions are correct and determine their significance and usefulness in selected sports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the Y-SprintREACT test (our assessment of agility performance) demonstrated good intersession test reliability in our sample of youth soccer players. Despite being classified as independent skills [6,10,11], the physical demands of both COD and agility performance are similar, challenging linear sprint, acceleration, and deceleration capacities [13,45]. When compared to human stimuli, reacting to generic light stimuli requires manipulation to body position, subsequently increasing the external loading on the knee when performing the cutting movement [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, also of importance during soccer match play is COD ability, defined as "the ability to change initial direction to a predetermined location and space on a field or court" [9]. Despite being misinterpreted in previous years, scientists have recently established agility and COD ability as independent skills [6,10,11], with little common variance [11][12][13][14]. Consequently, both qualities receive individual consideration when developing and assessing the physical qualities of team-sport athletes.…”
Section: Introductionmentioning
confidence: 99%